Le interazioni umani-ambiente nell’applicazione di tecniche agricole sapientemente adattate al territorio: l’esempio dell’isola di Pantelleria - Virginie Deguillame (Archivio Antropologico Mediterraneo)
The island of Pantelleria in Sicily challenges its residents with harsh conditions: lack of water sources, strong winds, drought, volcanic soils filled with stones. Despite these adverse conditions, local farmers have adapted unique agricultural techniques tailored to their environment. They understand nuances like soil types, wind patterns, and microclimates, in the pursuit of ensuring plant well-being. This enduring connection with their environment has shaped not only their agricultural practices but also their social organization, including marriage exchanges and property divisions. Although the changing global dynamics and evolving lifestyles that alter the island's landscape, the inhabitants of Pantelleria have demonstrated a remarkable resilience in maintaining traditional knowledge and related techniques, rooted in their agricultural heritage and deep attachment to the land. Geographical isolation, a bond with nature and social organization contribute to their identity, which evolves with the lifestyle choices of new generations.